Mineral Matter and Trace Elements in Coal - Shifeng Dai (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
Minerals are very significant components of coal from both academic and practical perspectives. Minerals may react when the coal is burned, either forming an ash residue, or, in many cases, releasing volatile components, or being needed to be removed as slag from the blast furnace during metallurgical processing. Minerals in coal can also be a source of unwanted abrasion, stickiness, corrosion, or pollution associated with coal handling and use. Minerals in coal, in some cases, are major carriers of valuable metals, such as Ga, Al, and rare earth elements, and these coals with highly-evaluated valuable metals have the potential to be raw sources for industry use. From the genetic point of view, the minerals in coal are products of the processes associated with peat accumulation and rank advance, as well as other aspects of epigenetic processes, and, thus, the minerals in coal can provide information on the depositional conditions and geologic history of individual coal beds, coal-bearing sequences, and regional tectonic evolution. This Special Issue, "Minerals in Coal", focuses on providing an up-to-date series of papers, covering research and technological developments in the nature, origin, and significance of the minerals in coal, and productions derived from combustion and gasification.